History of Islamic Educational Institutions and Their Contribution to the Development of Science - Tarikh Al Hafizh Hasibuan; Abdul Aziz Sebayang; Irwan Haryono S (Global Education Journal, 2026)
Islamic educational institutions have an important role in the process of transmission, development, and preservation of science throughout the history of Islamic civilization. This article aims to examine the development of Islamic educational institutions and their contribution to the advancement of science from classical to modern times. This research uses a qualitative approach with the library research method, by analyzing various relevant literature sources related to the history of Islamic education. The results of the study show that Islamic educational institutions such as kuttab, halaqah, madrasah, and pesantren have a strategic role in forming a systematic scientific tradition, both in the fields of religious science and rational science. In classical times, these institutions became centers for the development of various disciplines, such as philosophy, medicine, mathematics, and astronomy. Along with the times, Islamic educational institutions have undergone transformations in systems, curricula, and learning methods to adapt to the needs of society and the development of science. Thus, the history of Islamic educational institutions shows that these educational institutions not only function as a means of religious education, but also contribute significantly to the development of science and human civilization.